FRACTIONAL CAPUTO ANALYSIS OF DISCRETE SYSTEMS - Al-Maaitah, Amal F. (European Scientific Journal, ESJ, 2014)
In this paper we investigate the motion of discrete dynamical systems involving Caputo fractional derivatives using the fractional calculus. The fractional Hamilton’s equations and the explicit solutions of Euler-Lagrange equations are calculated by using the canonical transformations. The interesting point in this work is that the classical results are obtained when fractional derivatives are replaced with the integer order derivatives. Two examples are analyzed in detail.